2017
DOI: 10.1186/s12918-017-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating drivers of cell state transitions using gene regulatory network models

Abstract: BackgroundSpecific cellular states are often associated with distinct gene expression patterns. These states are plastic, changing during development, or in the transition from health to disease. One relatively simple extension of this concept is to recognize that we can classify different cell-types by their active gene regulatory networks and that, consequently, transitions between cellular states can be modeled by changes in these underlying regulatory networks.ResultsHere we describe MONSTER, MOdeling Netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The improved availability of African ancestry whole-genome sequence imputation reference panels available through initiatives such as the NHLBI-supported TOPMed program 52 should also provide high quality imputation of low and rare frequency variation in African ancestry populations, which will empower future studies. Lastly, we note better availability of other -omics datasets representing diverse ethnicities, such as transcriptomic data in tissue types relevant to asthma, will be needed to enable discoveries by utilizing the next generation of analysis tools 5355 .…”
Section: Discussionmentioning
confidence: 99%
“…The improved availability of African ancestry whole-genome sequence imputation reference panels available through initiatives such as the NHLBI-supported TOPMed program 52 should also provide high quality imputation of low and rare frequency variation in African ancestry populations, which will empower future studies. Lastly, we note better availability of other -omics datasets representing diverse ethnicities, such as transcriptomic data in tissue types relevant to asthma, will be needed to enable discoveries by utilizing the next generation of analysis tools 5355 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the comparative study of networks (inter-network relationships) is still a relatively young field. However, a number of recent studies have used linear approaches to analyze and cluster sets of networks (Marbach et al., 2012, Schlauch et al., 2017, Mucha et al., 2010, Onnela et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The resistant cells are characterized by the stabilization of the high expression of the marker genes, which were transiently high in the drug-naive pre-resistant cells (Figure 5A) (Shaffer et al, 2017). Studies using network inference of gene expression data have suggested that the genetic networks undergo considerable rearrangements upon cellular transitions or reprogramming (Moignard et al, 2015;Schlauch et al, 2017). We wondered if the transcriptional bursting model can explain how the transient high expression in drug-naive cells might become permanent upon treatment with anti-cancer drugs.…”
Section: Increasing Network Connectivity Leads To Transcriptionally Stable Statesmentioning
confidence: 99%